Does the relationship between sustainable human resource management and organizational identification vary by culture? Evidence from 35 countries based on GLOBE framework - Turek, Dariusz; Wojtczuk-Turek, Agnieszka; Edgar, Fiona; Podgorodnichenko, Nataliya; Okay-Somerville, Belgin; Fu, Na; Lupina-Wegener, Anna; Klein, Howard J.; Akbas, Gulcin; Al-Romeedy, Bassam Samir; Apospori, Eleni; Bosak, Janine; et al. (Emerald, 2025)
Purpose The article discusses the relationships between sustainable HRM and organizational identification, conceptualized at the individual level, and the moderating role of cultural dimensions conceptualized at the country level (described in GLOBE’s framework). The study’s theoretical model based on social exchange theory proposes that sustainable HRM practice increases organizational identification. However, the strength of this identification depends on the dimensions of national culture. Thus, we assumed national culture functions as a second-level moderator in the relationship between sustainable HRM and organizational identification. Design/methodology/approach We conducted the study with data from 10,421 employees across 35 countries. We used a multilevel modeling approach for data analysis. Findings The study revealed the cross-level interaction effects of national culture on the relationship between sustainable HRM practice and organizational identification. Specifically, the results indicate that sustainable HRM strengthens employees’ organizational identification more in cultures with higher levels of gender egalitarianism and lower levels of humane orientation. Originality/value This study demonstrates that the relationship between sustainable HRM practices and employees’ organizational identification is culturally sensitive. It highlights the need to consider cultural context when assessing the impact of sustainable HRM practices on employee outcomes. Furthermore, it shows that certain cultural dimensions can enhance the effect of sustainable HRM practices.
Keywords: Sustainable HRM practices; National culture; Organizational identification; fi=Henkilöstöjohtaminen|en=Human Resource Management|